The notion of denazification in Serbian print media in 2022-2023 - Todorovic, Vojislav; Ljubojevic, Ratko; Radovic Stojanovic, Jelena (Sociološki pregled, 2024)
One of the goals of the special military operation of the Russian Federation in Ukraine has been the denazification of Ukrainian society. The aim of the research is to determine how the media public in the Republic of Serbia saw denazification in relation to its factors: history, politics, economy, culture. Through a qualitative and quantitative analysis of media content, we have performed a descriptive identification of the term itself, as well as its frequency. Empirical research was carried out, which included five daily newspapers with the largest circulation in the Republic of Serbia: Novosti, Politika, Kurir, Blic and Danas, in the period from February 2022 to October 2023. The research indicates the active role of the print media in describing the concept of denazification, and the polarized attitudes of print media towards the denazification process, depending on whether they belong to mainstream or alternative print media, as well as the critical perception of the application of the National Socialist ideology in practice.
Keywords: denazification; Ukraine; print media; Serbia